Tuberculosis Mortality Hotspot Identification Tool - Kaur, Kirandeep Kulwant; Md Said , Salmiah; Syed Ismail, Sharifah Norkhadijah; Lim, Poh Ying (Multidisciplinary Applied Research and Innovation, 2022)
For more than a decade, tuberculosis (TB) has been the leading cause of death from a single infectious disease in Malaysia. The 2020 milestone of End TB Strategy of reduction of TB deaths by 35% compared to 2015 was not achieved by Malaysia. Instead the number of TB deaths reported in 2020 increased by 37% at national level and by 21% at state level of Selangor compared to their 2015 records. Spatial epidemiology has become indispensable in disease surveillance in developed countries. A tool to identify the Hotspots of TB mortality in Selangor state was developed in this research in alignment with the government’s strategy of intensifying research and innovation as priority issues in TB control under its National Strategic Plan (NSP) for Tuberculosis control (2016-2020). The use of population in the denominator enhanced the original TB distribution maps making them more robust and standardized. The knowledge gained from this can be used by health policymakers to make more informed decisions about resource allocation, type of control and, or interventions, and specific targeted areas. As a result, the existing TB burden will be reduced. Other states can then incorporate successful TB control programmes in Selangor by deploying GIS alongside their existing TB control programmes.